Spatio-temporal outbreaks of campylobacteriosis and the role of fresh-milk vending machines in the Czech Republic: A methodological study - Marek, Lukáš; Pászto, Vít (Geospatial health, 2017)
Inspired by local outbreaks of campylobacteriosis in the Czech Republic in 2010 linked to the debate about alleged health risks of the raw milk consumption, a detailed study was carried out. Firstly, scanning was utilised to identify spatio-temporal clusters of the disease from 2008 to 2012. Then a spatial method (geographical profiling originally developed for criminology) served as assessment in selecting fresh-milk vending machines that could have contributed to some of the local campylobacteriosis outbreaks. Even though an area of increased relative risk of the disease was identified in the affected city of České Budějovice during January and February 2010, geoprofiling did not identify any vending machines in the area as the potential source. However, possible sources in some nearby cities were suggested. Overall, 14 high-rate clusters including the localisation of 9% of the vending machines installed in the Czech Republic were found in the period 2008-2012. Although the vending machines are subject to strict hygiene standards and regular testing, a potential link between a small number of them and the spatial distribution of campylobacteriosis has been detected in the Czech Republic. This should be taken into account in public health research of the disease.
Keywords: Campylobacter Infections; Animals; Food Microbiology; Česká republika; Humans; Milk; epidemický výskyt choroby; potravinářská mikrobiologie; lidé; zvířata; mléko; Disease Outbreaks; Spatio-Temporal Analysis; kampylobakterové infekce; časoprostorová analýza; prodejní automaty na potraviny; Czech Republic; Food Dispensers, Automatic